PENGARUH INTERNET FINANCIAL REPORTING (IFR) TERHADAP NILAI PERUSAHAAN, HARGA SAHAM, FREKUENSI PERDAGANGAN SAHAM, DAN RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN LQ45 TAHUN 2015 - 2018) - Immanuela, Intan; Purbandari, Theresia (Widya Warta, 2020)
This study aims to empirically prove the influence of Internet Financial Reporting (IFR) on company value, the effect of IFR on stock prices, the effect of IFR on stock trading frequency, and the effect of IFR on stock returns. This study used the data from the company's financial statements included in LQ45 companies listed on the Indonesia Stock Exchange (IDX) during 2015-2018. The sampling technique used in this study was a purposive sampling method with several criteria, namely: 1) All companies listed in the LQ45 index in the 2015 - 2018 period, 2) Companies listed in the LQ45 index in the 2015 - 2018 period have website address that can be accessed, 3) Publishing financial information in rupiah units, 4) Having stock trading frequency â‰¥ 75 times in each quarter during the study period. A stock is said to be active if it has a frequency of trading shares â‰¥ 75 times each quarter, 5) Having complete information or data used in this study. Based on the sampling criteria of 45 companies listed in LQ45, the samples of this study consisted of 31 companies. This research used a simple regression analysis. The results proved that IFR had no effect on firm value, IFR had no effect on stock prices, IFR had no effect on the frequency of stock trading, IFR had no effect on stock returns.